Tingkat Pengetahuan dan Sikap Pada Penerapan Hygiene Perorangan Pengolahan Makanan di Hotel Bumi Senyiur Samarinda - Habibah Wahidah Aliefarada (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Personal hygiene is an action to maintain cleanliness and health, both physical and psychological. The goal is to maintain cleanliness, prevent contamination of dangerous bacteria from the body to the food being processed, and prevent disease. The aim of this research is to determine the level of knowledge and attitudes of food processing staff regarding the implementation of personal hygiene. This research is survey research, survey research is research that takes samples from a population and uses questionnaires as a data collection tool, one of the uses of survey research is for descriptive purposes. The sample is 12 food processing staff who work at the Bumi Senyiur Samarinda Hotel. Data collection uses questionnaires, questionnaires and observations. Analysis uses descriptive. Based on the results of descriptive analysis research, staff knowledge was 66.7% and staff attitude was 75%. For observation results, food processors got a value of 66.7%. In this way, the researchers found that the level of knowledge and attitudes of food processors at the Bumi Senyiur Samarinda Hotel generally obtained good results